The fragrant orchid Vanilla chamissonis : an appraisal of the genetic structure of wild populations from Osununú Natural Reserve, Misiones, Argentina - Cascales, Jimena
The commercial crops of vanilla face a significant risk of genetic erosion due to various factors. Vanilla chamissonis, a species with promising bioeconomic compounds, is found in limited regions in Argen-tina, particularly in the Osununú Natural Reserve in San Ignacio, Misiones, where it grows wildly in sectors (nuclei). This locally adapted germplasm of V. chamissonis holds considerable value and needs preservation efforts. In this study, we genetically characterized unexplored V. chamissonis germplasm and identified specimens within a phylogenetic framework using nuclear and plastid markers. The genotyping revealed that at least four gene pools contribute to the genetic diversity of these plants, with approximately 81% of total ge-netic variation allocated within populations. Sexual reproduction seems to predominate, and population N1 is a candidate for conservation. There is a genetic discontinuity between northeastern and southwestern nuclei, due to their different genetic constitutions and the tenuous isolation by distance. Phylogenetic results confirm the surveyed vanilla germplasm as V. chamissonis. This research provides essential insights for guiding the ongoing conservation and management efforts at the Osununú Reserve.